PENGUKURAN KINERJA KEUANGAN DENGAN METODE BALANCED SCORECARD DI PT. BANK PERKREDITAN RAKYAT (BPR) SINDANG BINAHARTA KOTA LUBUKLINGGAU - Indrawati Mara Kesuma; Arisky Andrinaldo; Ronal Aprianto; Siti Aisyah Azzahra (Jurnal AkunStie (JAS), 2020)
The purpose of this study is to determine performance measurement on financial perspective (Current Ratio, Return on Assets / Return on Investment and Return on Equity), customer perspective (customer acquisition level), internal business process perspective (manufacturing cycle efficiency) as well as learning and growth perspective (employee satisfaction levels and employee retention rates) using the Balanced Scorecard method at PT. People's Credit Bank (BPR) Sindang Binaharta, Lubuklinggau City. This research is qualitative in nature with the data source used primary and secondary data obtained from PT. People's Credit Bank (BPR) Sindang Binaharta, Lubuklinggau City. The results showed that the performance of PT. The Sindang Binaharta Rural Bank (BPR) of Lubuklinggau City using the Balanced Scorecard, namely financial perspective (current ratio is considered good, return on assets / return on investment is considered good and return on equity is not good), customer perspective is considered very good, business process perspective internal assessment has been run efficiently and finally the learning and growth perspective is considered very good.